2007
DOI: 10.1099/mic.0.2006/002261-0
|View full text |Cite
|
Sign up to set email alerts
|

Defect in early lung defence against Pseudomonas aeruginosa in DBA/2 mice is associated with acute inflammatory lung injury and reduced bactericidal activity in naïve macrophages

Abstract: Defect in early lung defence against Pseudomonas aeruginosa in DBA/2 mice is associated with acute inflammatory lung injury and reduced bactericidal activity in naïve macrophages

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 41 publications
(30 reference statements)
2
41
0
Order By: Relevance
“…Since DBA/2 mice are one of several C5-deficient inbred mouse strains (55), thus predicting a reduction in neutrophil recruitment to the lung tissues, the increased influx of inflammatory leukocytes we observed suggested that the loss of C5a may be compensated by the host by increasing the production of redundant/alternative neutrophil chemotactic factors.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Since DBA/2 mice are one of several C5-deficient inbred mouse strains (55), thus predicting a reduction in neutrophil recruitment to the lung tissues, the increased influx of inflammatory leukocytes we observed suggested that the loss of C5a may be compensated by the host by increasing the production of redundant/alternative neutrophil chemotactic factors.…”
Section: Discussionmentioning
confidence: 83%
“…Different techniques have been employed to introduce pathogens into the lung, such as intratracheal instillation (10), intranasal application (54), and application via aerosol (55,56). Intratracheal administration allows the colonization of the lung by a large fraction of the inoculum, with a potentially low level of extrapulmonary contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Following intratracheal infection, resistant mice showed a rapid influx of neutrophils (within 24 h) that was associated with clearance of bacteria. In contrast, Wilson et al (44) showed that, despite a similar neutrophil influx in both susceptible DBA/2 and resistant C57BL/6 mice during the initial phase of infection, only resistant mice cleared the bacteria, suggesting that there is a requirement for other host factors. Further, these authors showed that, although macrophages from susceptible mice are initially more phagocytic than C57BL/6 macrophages, they are defective for clearing or controlling bacterial colonization, indicating that rather than delaying the neutrophilic response, defective macrophages contribute to the susceptibility of DBA/2 mice to bacterial infection.…”
Section: Vol 78 2010mentioning
confidence: 90%
“…in S. aureus, the key factors are encoded by the Tnfaip8 and Seh1l loci (Ahn et al, 2010;Qiu et al, 2009), and in L. pneumophila, the critical marker is Naip5/Bircle (Zamboni et al, 2006). Third, the susceptibility of DBA/2 mice to the replication of some bacteria, including P. aeruginosa, is also not linked to the C5 deficiency (Wilson et al, 2007). Based upon our data, genetic crosses between the permissive and non-permissive mice can map and then help define host factors that govern susceptibility to S. maltophilia, with the potential for discovering new attributes of host susceptibility that have implications for explaining human cases of S. maltophilia disease.…”
Section: Resultsmentioning
confidence: 99%